LIVING WITH HIV AS A MAN: IMPLICATIONS FOR MASCULINITY - Mfecane, Sakhumzi (PINS-Psychology in Society, 2025)
This article examines constructions of masculinity by men living with HIV and using antiretroviral drugs (ARVs) in a South African rural village. It explores the impact of HIV on men’s lives, and discusses the implications of these impacts for understandings of masculinity. A total of 25 men were interviewed to explore their experience of living with HIV and the challenges posed by HIV sickness to their lives as men. Results show that the men’s lives changed dramatically following sickness from HIV and that these changes were perceived to negatively impact on various important markers of masculinity. In particular, the men’s provider roles and sexualities were perceived as significantly affected by HIV sickness. Drawing on current debates and theorising in the field of masculinity studies, the article interrogates the perceived threats to these markers and the participants’ responses to them.